(untitled) (Cardiovascular Journal, 2015)
Background: Diabetes mellitus is one of the most important risk factors of coronary artery disease. Admission hyperglycemia adversely influences the outcome of acute coronary syndrome patients. The study was conducted to compare the various diagnostic methods for the detection of undiagnosed diabetes mellitus in acute coronary syndrome patients with admission hyperglycaemia in Bangladeshi population. Methods: It was a cross sectional comparative study involving 157 patients with admission blood glucose level e7.8 mmol/l. Fasting plasma glucose, Glycated haemoglobin, pre-discharge oral glucose tolerance test was measured in all subjects and comparison of performance of different methods was done. Results: Oral glucose tolerance test revealed that in spite of admission hyperglycaemia, 57 (36.3%) patients were diabetic and 52 (33.12%) patients had impaired glucose homeostasis and 48 (30.57%) patients had normal glucose metabolism. Undiagnosed diabetes could not be adequately predicted with admission plasma glucose, fasting plasma glucose or HbA1c alone (area under the ROC curve 0.589, 0.825 and 0.852 respectively). Conclusion: Admission hyperglycaemia does not diagnose diabetes reliably in a stressful condition like acute coronary syndrome. Although neither admission plasma glucose, fasting plasma glucose, nor HbA1c level were as good as oral glucose tolerance test in detecting true diabetes, but combined fasting plasma glucose & HbA1c were found to be more sensitive & specific screening tool for detecting unknown diabetes in acute coronary syndrome patients with admission hyperglycaemia. Cardiovasc. j. 2015; 8(1): 35-42